H1N1 Influenza 폐렴 환자에서 발생한 Mycobacterium abscessus 감염 1예 - 정경원; 유훈; 이태훈; 권오성; 최석원; 강세훈; 심태선; 김동순; 송진우; Jung, Kyoung-Won; Yu, Hoon; Lee, Tae-Hoon; et al. (Tuberculosis and respiratory diseases, 2010)
Novel influenza A (H1N1) virus is a common pathogen of febrile respiratory infection recently. Here, we report the case of a 63-year-old male patient who presented with 3 days' ongoing cough and fever. He was diagnosed with novel influenza A (H1N1) pneumonia by real-time reverse-transcriptase-polymerase-chain-reaction (rRT-PCR). During treatment for novel influenza A (H1N1), his symptoms and radiologic findings improved initially, but multiple lung nodules developed subsequently and found on chest x-ray (on the 5th hospital day). Mycobacterium abscessus was isolated repeatedly from sputum and bronchoalveolar lavage fluid. To our knowledge, this is the first reported case of Mycobacterium abscessus lung disease in a patient with H1N1 influenza pneumonia.